SHEAR BEHAVIOR HOLLOW CORE REINFORCED CONCRETE BEAM - Wiku A. Krasna (INFO-TEKNIK, 2013)
I cross-section of reinforced concrete reduce weight and concrete needs, but the reduction in strength is not too large. Based on observations I section reinforced concrete beam is quite complicated and takes much longer time for the manufacturing. Therefore another form of cross-section which is equivalent to weight reduction in I cross-section concrete beam, with hollow square cross-section of reinforced concrete beam. It is expected that hollow square cross-section of reinforced concrete has a same strength with I cross-section of reinforced concrete. So this research may provide an alternative lightweight concrete beam, efficient in materials, easy installation in the implementation of shear reinforcement, and easy in formwork manufacture. This research was conducted to identify and compare the behavior of the shear of hollow core reinforced concrete beam with an I cross-section beam that equivalent with its. This experiment is using four reinforced concrete beam length 2000 mm, a T beam with bottom flange as control beam (BK) with measurement: bfa = 600 mm, bw = 125 mm, bfb = 200 mm, h = 300 mm, tf = 100 mm and three hollow core T beam as test beam (BB1, BB2 and BB3) with measurement: bf = 600 mm, bw = 200 mm, blubang = 75 mm h = 300 mm, tf = 100 mm. This experiment is testing the static and dynamic. Static loading is performed with a four-point system load, static loads are given by the hydraulic jack. Observations on the static load carried on the first crack and at each initial crack addition until the ultimate fracture. With the parameters used is the amount of deflection, the strain of reinforcing steel and concrete, the crack pattern that has happened.From the results of the experiments can be concluded that the hollow core reinforced concrete beam can be used as an alternative to I section reinforced concrete beam. It is seen from the difference in the shear load capacity is not much different between control beam (BK) and hollow beam (BB), with the difference between BK (299.3 kN) and BB1 (337.6 kN) is 12.79%, with BB2 (350, 6 kN) or 17.14% and with BB3 (289.4 kN) or -3.31%.